(untitled) (Global Journal of Management and Business Research, 2021)
The revolution of information and communication technology has played a leading role to transform the global economy towards digitalization: the digital economy. It#x2019;s considered as a driver of the modern economy to accelerate the economic growth of the nation. Nowadays, the traditional market has been replaced by a digital or online market with greater scope and confidence of the consumers. In the COVID-19 pandemic situation, it has already been proved that there is no alternative market place but online and the whole world solely depends on online economic activities.